Surface Patterning of Biomolecules Using Click Chemistry and Light‐Activated Electrochemistry to Locally Generate Cu(I). Issue 20 (23rd October 2020) - Gautam, Shreedhar; Lian, Jiaxin; R. Gonçales, Vinicius; Vogel, Yan B.; Ciampi, Simone; Tilley, Richard D.; Gooding, J. Justin
Abstract: Here we report a light‐assisted variant of click chemistry suitable for chemical patterning of semiconducting surfaces. Using a visible light beam to illuminate desired locations of an electrode surface, localized electrogeneration of the Cu(I) click catalyst was achieved. It was demonstrated that surface click reactions were correlated with a user‐defined 2D light pattern projected on a silicon photoelectrode. This new process is mask‐free and parallel, i. e., separate discrete regions of a semiconducting surface can be simultaneously reacted with a range of functional molecules. The covalent patterning of azido‐poly (ethylene glycol) molecules (PEG) over alkyne‐functionalized electrodes was employed as a proof‐of‐principle. By modulating the exposed chemical group of the clicked azido‐PEGs, the adhesion of antibodies and cells was further possible with spatial control. The use of structured light, instead of physical masks, drastically reduces patterning time to a couple of hours. Abstract : Light‐assisted click chemistry : A light assisted variant of click chemistry is developed for surface patterning of biomolecules. Spatial modulator enables parallel projection of light to drastically reduce the patterning time. Any user defined image can be translated into surface patterns simultaneously.